Is extra virgin olive oil a promising remedy for reducing the impact of postmenopausal osteoporosis? An experimental study - El-Shafaey, El-Sayed; Ali, Eman; Elkomy, Magda; Rizk, Mohamed Abdo; Altuwaijri, Saleh; Albarrak, Saleh (Frontiers in Veterinary Science, 2025)
IntroductionOsteoporosis, particularly postmenopausal osteoporosis, is a significant global health challenge with limited treatment options due to severe side effects associated with the long-term use of conventional therapies. Therefore, this study aims to provide a potentially novel therapeutic approach by examining olive oil's effects on bone mineral density (BMD), biochemical markers, biomechanical properties, and histopathological changes in an ovariectomized (OVX) rat model.MethodsIn this study, Twenty-four 6-month-old female Wistar rats were randomly allocated into four equal groups (n = 6 rats, for each group): control group, rats given 1mL/100g olive oil, ovariectomized rats (OVX-group), and OVX rats treated with olive oil. The femoral bone mineral density (BMD), biochemical parameters, biomechanical properties, and histopathological features were studied.ResultsAfter 3 months of extra virgin olive oil treatment, there were significant improvements in the different estimated parameters. This was demonstrated by preventing the changes in bone remodeling and BMD, improving the hormonal changes, oxidant/antioxidant imbalance, and abnormal levels of pro-inflammatory cytokines associated with OVX-induced osteoporosis. In addition, there was a marked improvement in the histological architecture of the cancellous and cortical bone appearance.ConclusionOlive oil dietary intake effectively reduces the impact of osteoporosis induced by ovariectomy in rats, suggesting a potentially feasible treatment option for postmenopausal osteoporosis that benefits bone architecture without any detrimental side effects on women's health.